2012
DOI: 10.1016/j.jval.2012.08.082
|View full text |Cite
|
Sign up to set email alerts
|

PHP31 Knowledge and Practice of Disposal of Date Expired and Unused Drugs

Abstract: OBJECTIVES: Knowledge and practice of disposal of date expired and unused drugs among college students and people having a health science background and to find the most widely used method of drug disposal for the expired drugs in the study group. METHODS: A pilot study questionnaire was prepared and a survey was done among students with Health Science background to understand the appropriateness of content. Further 500 University students and people having a health science background were interviewed personal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This is consistent with other studies in which respondents with knowledge of proper methods of drug disposal tend to return unused drugs to the pharmacy. On the other hand, studies have shown that the majority of respondents who do not have knowledge of proper methods for disposing of drugs are more likely to throw unused drugs into the garbage bin and sink or gave them away to other users than to return them to pharmacies …”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with other studies in which respondents with knowledge of proper methods of drug disposal tend to return unused drugs to the pharmacy. On the other hand, studies have shown that the majority of respondents who do not have knowledge of proper methods for disposing of drugs are more likely to throw unused drugs into the garbage bin and sink or gave them away to other users than to return them to pharmacies …”
Section: Discussionmentioning
confidence: 99%